Extraction and Characterization of Carrageenan from Seaweed (Kappaphycus alvarezii) Produced by South Lampung Indonesia Farmers and Utilization as a Tablet Binder using Metformin as a Drug Model - Kurniawan, Dhadhang W.; Rasyid, Kharisma Aditya; Santosa , Rizqi Agus; Sunarto (Iraqi Journal of Pharmaceutical Sciences, 2024)
Indonesia is known as one of the countries which has the biggest biodiversity worldwide. The aim of this study is to determine the characteristics and the strength of carrageenan as a tablet binder from Kappaphycus alvarezii seaweed that is produced by farmers in the South Lampung District, Province of Lampung. Carrageenan that was produced was characterized by its physical, chemical, and functional characteristics. Carrageenan then was formulated in a tablet dosage form as a binder and compared to tablets that used carbopol as a binder. The data obtained from the physical, chemical, and functional characteristics was described qualitatively and the test results of some parameters from the physical characteristic tablets were analyzed theoretically as compared to the standard literature. The statistical tests used an independent T-test at 95% of the confidence interval. The results showed that carrageenan has the following characteristics: pH 10.7; moisture content of 5.001%; particle size distribution of 76.8% (120 mesh); compressibility index of 21.9%; inflate index of 240% (pH 1.2); repose angle of granule is 30,48o; flow rate of 5 g/s; viscosity at 45.922,85 cps (75oC) and 53.690 cps (50oC); SEM results indicate that carrageenan particle shape was irregular; FTIR showed that there were ester sulfate, 3,6- anhydrogalactose, and galactose-4-sulfate. Based on the result, it was concluded that the metformin tablet that was made using carrageenan and carbopol as binders qualified the physical characteristic of tablets, but there were significant differences in granule flow rate, tablet disintegration time, and dissolution profiles of tablets.